Drug‐induced acute pancreatitis: results from the hospital‐based Berlin case–control surveillance study of 102 cases. Issue 7 (19th August 2013) - Douros, A.; Bronder, E.; Andersohn, F.; Klimpel, A.; Thomae, M.; Ockenga, J.; Kreutz, R.; Garbe, E.
Summary Background Drug toxicity is a well‐known cause of acute pancreatitis (AP). Although many drugs have been associated with AP, the magnitude of the risk of most of them remains largely unknown. Aim To determine the pancreatotoxic risk of a wide range of drugs. Methods The hospital‐based Berlin case–control surveillance study, including all 51 Berlin hospitals in a hospital network, ascertained 102 cases with idiopathic AP (IAP) and 750 controls between 2002 and 2011. Patients with IAP were thoroughly validated using anamnestic, clinical or laboratory data. Drug exposure was obtained in a face‐to‐face interview. Possible drug aetiology was assessed in individual patients through a standardised causality assessment applying the criteria of the World Health Organization. Drug risks were further quantified [odds ratios (OR) with 95% confidence intervals (CI)] in a case–control design with unconditional logistic regression analysis. Results The pancreatotoxic risk of several drugs, including azathioprine (OR 5.1; 95% CI 1.9–13.5), fenofibrate (OR 12.2; 95% CI 2.3–69.1), mesalazine (OR 3.3; 95% CI 1.1–9.5) or angiotensin‐converting enzyme inhibitors, was corroborated by case–control analysis and causality assessment. Causality assessment suggested a pancreatotoxic potential, among others, for mercaptopurine or the seldom reported leflunomide, and alluded to a novel risk for tocilizumab. Case–control analysis showed an increased risk for two phytotherapeutics: harpagophytum and valerian radix. Conclusions Our study quantified the pancreatotoxic risk of different drugs and phytotherapeutics. The findings corroborate previous results from the literature but also indicate risks for substances not previously reported, highlighting the need for further controlled studies on pancreatic toxicity.